Social and Vocational Integration of Special Needs Students: Array - Voicu, Valentina-Ștefania (New Trends in Psychology, 2020)
As we approach a new age of inclusion and diversity regarding other groups of people that are discriminated against because of etnicity, religion, gender and so forth, we must not exclude people that also need help from the community they live in: people with special needs. In order for these people to properly function as members of the society they live in they must be helped in their most critical stages of preparation prior to becoming active in a work field.